The Relationship between Learners’ Starting Age in Learning Second Language and Their Choice of Language Learning Strategies (LLS) - Dian Palupi; Anita Triastuti; Laser Romios (Makassar State University, 2021)
Abstract. Age and the choice of language learning strategies (LLS) have similarities with the relationship between the aspects of individual differences, social factor, and the LLS itself. This study aimed to investigate whether and how the learners’ starting age in second language learning affects their choice of LLS. 94 ESL learners of two age-based groups were involved in this study. A translated version of the Strategy Inventory for Language Learning (SILL) version 7.0 proposed by Oxford and an interview guideline were used in data collection. Such version covers 50 statements designed for the learners of English as a second and foreign language. The SILL identified the learners’ strategy by asking them to give a response to a series of strategy statements. The data were then analyzed through inferential statistics. The results of the study revealed that learners’ starting age in second language learning affects their choice of LLS due to their different goals in learning English. The early-starting learners generally learn English to communicate properly while the late-starting learners do the same for specific purposes, such as for working and for studying abroad. Keywords: Starting Age, Language Learning Strategies, Second Language Acquisition